Antihiperkolesterolemia Kombinasi Ekstrak Etanol Daun Biduri (Calotropis gigantea L.) dan Bidara (Ziziphus spina-christi L.) pada Mencit - Sisilia Oktaviani Rahastri; Cicik Wijayanti; Gaby Ayu Patricia; Khoirul Ngibad (JURNAL FARMASI DAN MAKANAN, 2025)
Hyperlipidemia is a major risk factor for cardiovascular diseases, highlighting the need for safe and effective cholesterol-lowering agents. This study aimed to evaluate the effectiveness of Calotropis gigantea (biduri) and Ziziphus spina-christi (bidara) leaf extracts in reducing cholesterol levels in male mice. The leaf powders were extracted with 96% ethanol using maceration for 3x24 hours, yielding 6.8% and 3.1% extract, respectively. A total of 36 male mice were divided into six groups: negative control, positive control (propylthiouracil), drug control (simvastatin), and three treatment groups receiving 14, 28, and 56 mg/20 g body weight (BW) of extract. Cholesterol levels were measured using a spectrophotometer. Results showed that cholesterol increased to 189.3 mg/dL in the positive control, while simvastatin reduced it to 117.7 mg/dL. Both biduri and bidara extracts decreased cholesterol in a dose-dependent manner, with the highest dose (56 mg/20 g BW) reducing levels to 150.5 mg/dL, or 20.4%. This effect is likely due to flavonoids, saponins, and alkaloids that inhibit cholesterol absorption and enhance bile excretion. The study concludes that biduri and bidara leaf extracts have potential as effective and safe natural cholesterol-lowering agents.